Dynamics of a subtropical population of the purse crab Persephona punctata (Decapoda: Brachyura: Leucosiidae) in Southeastern Brazil - Júlia Fernandes Perroca; Daphine Ramiro Herrera; Antonio Leão Castilho; Rogerio Caetano da Costa (Nauplius, 2020)
ABSTRACT This study investigated the population dynamics of Persephona punctata with emphasis on population structure, sex-ratio, spatial distribution, maturity and reproductive period. Crabs and environmental factors (i.e., water temperature and salinity, and sediment texture and organic matter content) were collected monthly, from July 2012 to June 2014 in four sites within the Federal Environmental Protection Area of Cananéia-Iguape-Peruíbe: located in the oceanic area adjacent to the Cananéia region. The population had a female-biased sex-ratio. Persephona punctata had a seasonal reproduction and the higher percentage of ovigerous females (OF) occurred in spring and summer. There was a positive correlation (“lag 0”) between temperature and number of OF (cross-correlation, p < 0.05) and a negative correlation between salinity and OF (“lag-2”), suggesting that periods of higher salinity may be favorable to larval hatching. The estimated size (carapace width - CW50) at the onset of gonadal maturity of males (35.0 mm) was larger than that of females (30.1 mm), which is a common feature of Brachyura. Our results extend the knowledge on the life history of P. punctata and may be useful for the development of future mitigation measures aimed at its conservation.